Environmental Law Enforcement Based on Law Number 32 Of 2009 and the Challenges of the Industrial Revolution 4.0 - Yonnawati Yonnawati (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
Law functions to protect various human interests and is implemented in both peaceful conditions and when violations occur. The decline in environmental quality due to the exploitation of natural resources is often justified in the name of people's welfare. This condition raises demands for effective environmental law enforcement amid the challenges of the Industrial Revolution 4.0. This research aims to analyze the impact of pollution and weak law enforcement, as well as examine the role of technology in improving legal effectiveness and formulating adaptive regulatory strategies in the digital era. This research employs a qualitative-descriptive approach, utilizing a library research method and inductive-deductive analysis, informed by various literature sources. The effectiveness of environmental law depends on fundamental principles, the application of technology, and collaborative law enforcement. Digital technology and industrial automation can strengthen the monitoring and transparency of ecological law if developed with an inclusive and fair approach. Law No. 32/2009 remains relevant, but requires adaptive policies. Keywords: Environmental Law, Industry 4.0, Revolution